Identification of Peripheral Anterior Synechia by Corneal Deformation Using Air-Puff Dynamic Anterior Segment Optical Coherence Tomography - Ye, Shuling; Bao, Chenhong; Chen, Yulei; Shen, Meixiao; Lu, Fan; Zhang, Shaodan; Zhu, Dexi (Frontiers in Bioengineering and Biotechnology, 2022)
Indentation gonioscopy is commonly used in clinic to evaluate peripheral anterior synechia (PAS) of angle closure glaucoma (ACG). The examination requires contacting with cornea resulting in uncomfortable feeling for patients, and it only provides qualitative outcomes which may be affected by subjective judgment of the clinicians. Previous studies had reported to identify the presence of PAS by measuring the changes of morphological parameters of anterior chamber angle (ACA) under the pupillary light reflex, using anterior segment optical coherence tomography (AS-OCT). However, this method was invalid for some subjects who had low sensitiveness to light. This article describes an air-puff dynamic anterior segment optical coherence tomography (DAS-OCT) system that can evaluate the presence of PAS in non-contact approach. Peripheral cornea is deformed by air puff jetted from the DAS-OCT, causing a transfer of force to the ACA, just as how the indentation gonioscopy works. The dynamic changes of ACA before and after the air puff are recorded by OCT. Ten eyes of normal subjects were enrolled in this study to validate the repeatability and availability of the measurements. Then ten samples of ACA from five subjects with ACG were recruited, and were assigned into two groups, non PAS group (NPAS) and PAS group, according to the results of gonioscopy. The ACA structural parameters including angle opening distance at 750 μm to the scleral spur (AOD750) and trabecular-iris space area at 750 μm anterior to the scleral spur (TISA750) were then calculated automatically by a custom-written algorithm. The intraclass correlation coefficient (ICC) of measured parameters were all above 0.85 for normal subjects, exhibiting good repeatability. For patients, both parameters showed significant differences between the two groups after air puff, while no differences before air puff. AOD750dif and TISA750dif between two groups showed more significant differences, indicating that they could be used as indicators to identify the presence of PAS. In conclusion, the DAS-OCT system proposed in this study is demonstrated effective to identify the presence of PAS by measuring the changes of ACA via noncontact approach. It shows great potential for applications in guidance for diagnosis of angle closure glaucoma.